The effect of uncertainty and resource constraints on concurrent engineering projects. (1st October 2007) - Kara, Sami; Kayis, Berman
Concurrent Engineering (CE) requires careful planning and analysis due to the uncertainties caused by the parallel execution of activities. In this paper, a probabilistic mathematical model fitted to precedence relations is proposed to estimate the project completion time under uncertainty and resource constraints. A computer program was prepared in C++ to simulate the randomness in the process. The major benefits of the model developed are two-fold. Firstly, it allows users to consider uncertainty and resource constraints before CE implementation. Secondly, trade-off analysis between resources available vs. project completion time can be carried out in advance to allocate resources accordingly.